Global assays of fibrinolysis. (12th May 2017) - Ilich, A.; Bokarev, I.; Key, N. S.
Abstract: Fibrinolysis is an important and integral part of the hemostatic system. Acting as a balance to blood coagulation, the fibrinolytic system protects the body from unwanted thrombus formation and occlusion of blood vessels. As long as blood coagulation and fibrinolysis remain in equilibrium, response to injury, such as vessel damage, is appropriately regulated. However, alterations in this balance may lead to thrombosis or bleeding. A variety of methods have been proposed to assess fibrinolytic activity in blood or its components, but due to the complexity of the system, the design of a "gold standard" assay that reflects overall fibrinolysis has remained an elusive goal. In this review, we describe the most commonly used methods that have been described, such as thromboelastography (TEG and ROTEM), global fibrinolytic capacity in plasma and whole blood, plasma turbidity methods, simultaneous thrombin and plasmin generation assays, euglobulin clot lysis time and fibrin plate methods. All of these assays have strengths and limitations. We suggest that some methods may be preferable for detecting hypofibrinolytic conditions, whereas others may be better for detecting hyperfibrinolytic states.